A New Method for the Sputum Cytology Test Without Direct Contact to Specimens During COVID-19 Pandemic - Cui, Junqi; Wang, Xia; Rao, Yamin; Ji, Tianhai; Li, Long (Frontiers in Medicine, 2022)
Background Coronavirus disease 2019 (COVID-19) pandemic continues to spread across the world. Specimens of blood, body fluids and excreta received in the department of pathology undoubtedly increased the risk of infection, especially in some hospitals that are short of professional protection capability. Here we provided a new simple way for the sputum cytology test during the COVID-19 pandemic. Methods Sputum samples from 30 patients with lung cancer were collected and divided into two groups, including the control group and the experimental group. Samples of the control group were processed in the biological safety cabinet, while the experimental group was put into the sealed specimen bag directly and pretreated with 75% medical alcohol. Then the cell morphology and tumor cell identification were analyzed by cell smears and liquid-based cell staining. The expression of cell antigens was determined by immunohistochemical staining. Result Our result showed that both sputum samples in two groups exhibited complete cell structure and clear morphology according to the cell smear and liquid-based cell staining. In addition, the immunohistochemical result showed that cell antigens, including cytokeratin (CK), leukocyte common antigen (LCA), and thyroid transcription factor-1 (TTF1), were specifically expressed in the cell membrane, cytoplasm, and nucleus, respectively. The tumor cells were distributed diffusely, and cell antigens were located accurately after pretreatment with 75% medical alcohol and were consistent with that of the control group. Conclusion Using 75% medical alcohol to pretreat sputum specimens has no obvious impact on cell morphology and antigens expression. Our study provided a new method for the sputum cytology test with no direct contact so as to protect medical staff against the virus during COVID-19 outbreak.